Job Satisfaction among Royal Malaysia Air Force Personnel at Pangkalan Udara Sendayan - Fatimah, Pauzi (2020)
Job satisfaction is a positive and favourable feeling towards one‟s job. Satisfied personnel perform better and retain longer in their job. This paper focuses on Royal Malaysia Air Force (RMAF) personnel at Pangkalan Udara Sendayan due to increasing disciplinary related cases among personnel such as absent without leave (THTC), criminal cases and loan defaulter. Relationship with peers, superior subordinate relationship, organizational climate, and economy rewards were tested towards job satisfaction among personnel. The research instrument used in this study is a questionnaire adopted and adapted from Mahussain (2007) on military discipline affecting military personnel. Questionnaires were sent to personnel using online survey form. The results indicated that all independent variables are related to job satisfaction with economic rewards as the most influential variable to job satisfaction, followed by organizational climate and superior-subordinate relationship. However, relationship with peers is an influential factor towards job satisfaction